2001
DOI: 10.1161/01.str.32.4.964
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life After Stroke A Comprehensive Review

Abstract: Background and Purpose-We performed a comprehensive review of all quality-of-life (QOL) estimates for stroke appearing in the peer-reviewed literature between 1985 and 2000. We examine variation in QOL weights and the rigor of methods used to assess QOL and discuss the implications for cost-utility assessment and resource allocation decisions. Methods-Through a systematic search, we identified 67 articles that met our inclusion criteria. A team of trained researchers read each article and followed detailed gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
1
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(101 citation statements)
references
References 83 publications
3
91
1
6
Order By: Relevance
“…194 The first review included 67 articles. 192 Quality of life estimates ranged from -0.02 to 0.71 for major stroke (n = 67), from 0.12 to 0.81 (n = 14) for moderate stroke, from 0.45 to 0.92 for minor stroke, and from 0.29 to 0.903 for any stroke. An important difference between the estimates was 145 that is, whether patients valued their own state or valued hypothetical condition-specific or generic states.…”
Section: Quality Of Lifementioning
confidence: 97%
See 1 more Smart Citation
“…194 The first review included 67 articles. 192 Quality of life estimates ranged from -0.02 to 0.71 for major stroke (n = 67), from 0.12 to 0.81 (n = 14) for moderate stroke, from 0.45 to 0.92 for minor stroke, and from 0.29 to 0.903 for any stroke. An important difference between the estimates was 145 that is, whether patients valued their own state or valued hypothetical condition-specific or generic states.…”
Section: Quality Of Lifementioning
confidence: 97%
“…192,193 It is currently recommended for economic valuation that health state utility values should be obtained using a choice-based technique such as standard gamble (SG) or time trade-off (TTO) rather than a rating scale. 194 The first review included 67 articles.…”
Section: Quality Of Lifementioning
confidence: 99%
“…82 The review reports the results of 67 studies which provide 161 utility estimates for stroke. The model uses the median value from the range of utilities presented for minor, moderate and major stroke.…”
Section: Source Of Effectiveness Datamentioning
confidence: 99%
“…The studies used in Tengs and colleagues' review 82 were available on request from the author. By reviewing these, it is revealed that the utility of major stroke of 0.36 applied in the model was that reported in a study using an RS in members of the community.…”
Section: Utilitymentioning
confidence: 99%
“…Некоторые авторы используют порядко-вую шкалу тяжести инсульта Rankin, где зна-чение «0» присваивается бессимптомному инсульту, а значение «6» -смертельному по-ражению (Tengs et al, 2001) 2008) от-метили, что наихудшие показатели качества жизни были выявлены у пациентов, перенес-ших обширные инсульты в бассейне передней мозговой артерии, а также при наличии пато-логии эмболической этиологии. Отрицательно влияющими на качество жизни факторами являются депрессия и большой объем потери серого вещества подкорковых ядер (Irimia, Van Horn, 2014).…”
unclassified